Overview of Environmental Conditions and Personal Hygiene for the Presence of Pathogenic Germs in Food at Tanggo Rajo Culinary Tourism - Putri, Fitria Eka; Maulidya Istiqomah, Nuralifah; Sari, Puspita; Hubaybah, Hubaybah; Hidayati, Fajrina (RRZ Scientific Publishing, 2024)
Foodborne disease refers to a condition when the body is affected by microbial toxins or substances that enter through the consumption of food. The World Health Organization (WHO) has reported that around 1 in 10 individuals worldwide fall ill and experience 420,000 fatalities annually due to foodborne illnesses or food poisoning. Additionally, these incidents result in a loss of 33 million years of healthy life each year. The objective of the study is to assess the ambient and personal hygiene conditions and their impact on the presence of harmful microorganisms in food during culinary excursions in Kanggano Rajo. This study was employed a quantitative research approach with a descriptive design and a cross-sectional research design. The study population consists of 101 individuals engaged in the street vendors culinary items during the Culinary Tour of Tanggo Rajo. The findings indicated that 68.5% of the respondents needed to fulfill their hygiene preferences. Additionally, study was reported unsuitable environmental sanitation conditions, 57.4% reported inadequate water condition, 77.8% reported improper waste handling, 81.5% reported inadequate waste disposal, and 100% reported insufficient vector control. The microbiological test results revealed the presence of Enterobacter Hafniae in 2 samples, enterobacter aerogenes in 16 samples, and Klebsiella Azaenae in 36 samples. Empowering and enhancing education in all critical sectors is advisable while ensuring effective monitoring and evaluation.